Lipid nanoparticles for antisense oligonucleotide gene interference into brain border-associated macrophages - Calero, Macarena; Moleiro, Lara H.; Sayd, Aline; Dorca, Yeray; Miquel-Rio, Lluis; Paz, Verónica; Robledo-Montaña, Javier; Enciso, Eduardo; Acción, Fernando; Herráez-Aguilar, Diego; Hellweg, Thomas; Sánchez, Luis; et al. (Frontiers in Molecular Biosciences, 2022)
A novel colloidal synthesis based on the Bligh-Dyer emulsion inversion method was designed for integrating into lipid nanoparticles (LNPs) cell- permeating antisense single-stranded DNAs –also known as GapmeRs (GRs) for mRNA interference. The GR@LNPs were formulated as an interferential therapeutic platform targeted towards brain perivascular and meningeal macrophages for silencing inflammation-related genes. We aim at inhibiting the expression of the gene encoding for lipocalin-type prostaglandin D synthase (L-PGDS), an anti-inflammatory enzyme expressed in the border central nervous system macrophages whose level of expression is altered in inflammatory -related neuropsychopathologies such as depression and schizophrenia. We synthetized GR@LNPs functionalized with mannosylated lipid as a specific ligand for the macrophage surface receptors to facilitate its selective phagocytosis. The novel nanoobjects show a high GR-packing density in a compact multilamellar configuration as evaluated by light-scattering, zeta-potential and transmission electronic microscopy. In the preclinical setting, the GR@LNPs were tested in vivo by intracerebroventricular injection in Wistar rats. Immunofluorescence studies revealed the localization of GR@LNPs in perivascular and meningeal macrophages. Their ability to inhibit L-PGDS gene expression was verified by in situ hybridization performed in rat prefrontal cortex. Compared to conventional GapmeR-delivery systems, a reduction of L-PGDS mRNA expression was found in the cortical brain areas of rats receiving GR@LNPs. The novel GR@LNPs are expected with a bioorthogonal activity as reacting with L-PGDS gene transcripts inside the living system without interfering other genetic or biochemical circuitries. The results pave the way in novel gene therapy platforms for advanced treatments of neuroinflammation-related pathologies.